Peripheral Blood Eosinophilia and Long-term Severity in Pediatric-Onset Inflammatory Bowel Disease. Issue 12 (21st January 2020) - Prathapan, Krishnapriya Marangattu; Ramos Rivers, Claudia; Anderson, Alyce; Koutroumpakis, Filippos; Koutroubakis, Ioannis E; Babichenko, Dmitriy; Tan, Xiaoqing; Tang, Gong; Schwartz, Marc; Proksell, Siobhan; Johnston, Elyse; Hashash, Jana G; et al.
Abstract: Background: Peripheral blood eosinophilia (PBE) is a biomarker of an aggressive multiyear natural history in adults with inflammatory bowel diseases (IBDs). Additionally, PBE at diagnosis is associated with higher disease activity in pediatric-onset IBD. We sought to determine if PBE can function as a biomarker of long-term disease severity in pediatric-onset IBD patients who are followed into adulthood. Methods: We analyzed a consented, prospective, natural history IBD registry at an adult tertiary center from 2009 to 2018. Prevalence of PBE was evaluated in both pediatric- and adult-onset IBD patients. Demographics, clinical characteristics, and health care utilization data were compared in patients with and without PBE. Results: Among 2800 adult IBD patients, 23.4% had pediatric-onset disease. PBE was found in 34% of the pediatric-onset patients compared with 26.8% of the adult-onset IBD patients ( P < 0.001). In the pediatric-onset IBD cohort, PBE was associated with higher rates of allergies ( P < 0.0001), but not of asthma, allergic rhinitis, or primary sclerosing cholangitis. In the adult IBD patients with pediatric-onset disease, PBE was associated with higher rates of C-reactive protein elevation ( P < 0.0001), erythrocyte sedimentation rate elevation ( P < 0.0001), higher health care utilization, and higher average health care charges per year ( P < 0.00001). Conclusions: Peripheral blood eosinophilia was more prevalent in adult IBD patients with pediatric-onset compared with adult-onset disease. Among all IBD patients with long-term follow-up, PBE defined a subgroup with more severe illness. These data suggest that PBE may be a biomarker for a high-risk subgroup with high cost trajectory and long-term severity in pediatric-onset IBD that persists into adulthood.